Indian and Oriental studies in a Euro-Indian perspective for the 21st century - Byrski, Maria Krzysztof Krzysztof (Acta Orientalia Vilnensia, 2008)
Collegium Civitas; University of Warsaw The basic presumption is the need in Oriental studies to go much further than mere description of different civilisations. They should be compared with our own, and the question of whether the concepts evolved by those civilisations can help us better understand the reality in which we actually happen to live should be asked. For the adoption of this approach to the study of South Asia, it is suggested that European and Indian civilisations are ‘twins-unlike’. The paradox is intended since certain—so to say—general structural aspects of both civilisations are similar (geographical magnitude, variety of climate, size of population, and its anthropological, ethnic, linguistic and religious diversity), but as far as content is concerned they are of course very much unlike each other. The conclusion of our comparison is that Indian traditional civilisation is that of sustenance and containment while the European one is that of progress, development and expansion. Proper synergy of the two tendencies is postulated for sustainable development to be achieved.